The Influence of Digital Transformation and Free Cash Flow on Cost Stickiness Moderated by Firm Complexity - Yosua Samuel Ramli; Theresia Olivia (PT FORMOSA CENDEKIA GLOBAL, 2025)
In the era of globalization and rapid technological advancement, digital transformation has become a crucial strategy for companies to enhance operational efficiency and competitiveness. Implementing technologies like automation, big data, and artificial intelligence (AI) enables companies to cut expenses and enhance productivity. However, not all companies are able to optimally adjust their cost structures, especially amid market demand fluctuations, such as those experienced during the Covid-19 pandemic. This study aims to analyze the effect of digital transformation and free cash flow on the level of cost stickiness in manufacturing companies, with firm complexity as a moderating variable. The study also considers control variables such as profitability and firm size to provide a more comprehensive analysis. A quantitative approach is employed in this research, utilizing secondary data sourced from the financial reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2022. A total of 43 manufacturing companies were analyzed. Data processing was carried out using EViews version 10. The results show that digital transformation has a negative effect on cost stickiness. Conversely, free cash flow has a positive effect on cost stickiness, indicating that excess liquidity may lead to higher fixed costs during periods of declining activity. Firm complexity is not proven to significantly strengthen the relationship between the independent variables and cost stickiness, despite being theoretically relevant.